Condylar Aplasia and Hypoplasia: A Rare Case. (24th March 2013) - Shivhare, Peeyush; Shankarnarayan, Lata; Usha; Kumar, Mahesh; Sowbhagya, Malliger Basavaraju
Abstract : Aplasia of condyle is very rare, when this condition not seen as a part of a syndrome. We report a case of condylar aplasia on the right side and hypoplasia on the left side in a 21-year-old female. The patient reported to the department with a chief complaint of underdeveloped lower jaw. Clinical examination, conventional radiographs, and 3D CBCT images revealed complete absence of condyle on the right side and hypoplasia on the left side.